High-weather-resistance ASA rubber powder and preparation method thereof

By adopting a three-layer structure, the combination of core layer, core layer and shell layer and modified nanomontmorillonite and antioxidants, the problem of low weather resistance of ASA resin is solved, and the harsh environment is achieved high performance and long-life material preparation.

CN119143943APending Publication Date: 2024-12-17BINZHOU YONGHONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476136.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing ASA resin has low weather resistance and is difficult to meet the needs of use in harsh environments, especially in the fields of automobiles and outdoor building materials. The existing preparation methods are complex and difficult to control particle size and structure, which affects the impact strength and flowability of the material. .

Method used

High weathering ASA powder with a three-layer structure is composed of a core layer, a core layer and a shell layer. The core layer is added with silicone rubber latex, and the shell layer is grafted and modified nanomontmorillonite and composite antioxidants. The preparation method is optimized. Significantly improve weather resistance.

Benefits of technology

On the basis of ensuring impact strength and fluidity properties, the weather resistance of ASA particles is significantly improved, the service life of the material is extended, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096166210000172
    Figure BDA0005096166210000172
  • Figure BDA0005096166210000181
    Figure BDA0005096166210000181
Patent Text Reader

Abstract

The invention provides high-weather-resistance ASA rubber powder and a preparation method thereof, and relates to the technical field of high polymer material processing. The high-weather-resistance ASA rubber powder is of a three-layer structure comprising a core layer, a core layer and a shell layer from inside to outside, the particle size of the high-weather-resistance ASA rubber powder is 400 to 600 nm; the core layer is prepared from the following raw material components in parts by weight: 30 to 45 parts of styrene; 10 to 20 parts of acrylonitrile; 0.2 to 1.5 parts of an emulsifier; 0.1 to 0.5 part of trimethylolpropane trimethacrylate; 0.8 to 1.5 parts of vinyl triethoxy silane; 15 to 25 parts of silicone rubber emulsion; 0.2 to 0.6 part of an initiator; and 30-50 parts of water. The weather resistance of the ASA colloidal particles is remarkably improved while the impact strength of the ASA colloidal particles is ensured by optimizing the monomer components and the proportion and optimizing the preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material processing, and in particular to a highly weather-resistant ASA rubber powder and a preparation method thereof. Background Art

[0002] ASA rubber powder is a ternary polymer composed of acrylate (A), styrene (S) and acrylonitrile (A). ASA rubber powder is a typical core-shell impact modifier, in which the core is an acrylic rubber and the shell is a grafted copolymer of styrene and acrylonitrile. The performance of ASA rubber powder is similar to that of ABS rubber powder, both of which have good mechanical properties, processing properties, electrical insulation properties, chemical resistance, and coloring properties. ASA rubber powder can not only be used as a toughening modifier to modify thermoplastics such as polyvinyl chloride, polycarbonate, and nylon, but can also be blended with styrene-acrylonitrile copolymers to make ASA engineering resins, which are widely used in the fields of automobiles, electronic appliances, outdoor building materials, etc.

[0003] Chinese patent CN 113150460 A discloses a method for preparing ASA resin. In the synthesis of ASA graft copolymer, diene monomers are used to replace traditional crosslinking agents and grafting agents. While improving the crosslinking degree and grafting efficiency of ASA resin, the glass transition temperature of polyacrylate copolymer is reduced, thereby comprehensively improving various properties of ASA resin. The impact strength of ASA resin after the improved process is greater than 10KJ / m 2 , reaching the level of imported ASA resin. However, it is not enough for ASA resin to have only high impact strength, it must also have good weather resistance to adapt to various application scenarios.

[0004] Chinese patent CN 109897141 A relates to a method for preparing an ASA resin, specifically a method for preparing an agglomerant with a specific structure, and a method for preparing a high-strength ASA resin by regulating the particle size of acrylic rubber through the agglomerant. The technical principle of the invention is to achieve the following two functions in the process of preparing the agglomerant: the first is to ensure that the carboxylic acid group is on the surface of the agglomerant particles as much as possible, so as to facilitate the fusion of the interface between the agglomerant particles and the agglomerated particles; the second is to introduce an organic siloxane monomer into the agglomerant so that the agglomerant latex particles have a higher strength after subsequent fusion. The agglomerant emulsion described in the present invention is used for the agglomeration of butyl acrylate emulsion, and the agglomerated latex is grafted with styrene and acrylonitrile to obtain an ASA resin. The mechanical properties of the ASA resin of the technical solution are tested to be higher than the ASA resin obtained by the conventional agglomeration method. This ASA resin containing siloxane groups is particularly suitable for the fields of building materials such as coatings, concrete, and resin tiles. In this case, not only is there a requirement for its strength, but also a requirement for good weather resistance to extend the service life of the material.

[0005] The core of ASA resin lies in the preparation of ASA rubber powder. Its technical bottleneck is mainly the core-shell structure, particle size control and dispersion, wetting and compatibility of its matrix plastic. It is a systematic research and development and production project. At present, the preparation methods of ASA resin high rubber powder mainly include: emulsion blending method and grafting method. At present, the grafting method is mainly used for preparation, and the grafting method is divided into bulk polymerization method, suspension polymerization method and emulsion polymerization method. Bulk polymerization and suspension polymerization are difficult to obtain high-quality products because the rubber particle size is not easy to control. The emulsion grafting polymerization method is conducive to controlling the reaction rate and the distribution of particle size. The emulsion grafting polymerization method can also be divided into one-step polymerization method and multi-step polymerization method. Since the one-step polymerization method is difficult to control the reaction rate, the number of latex particles in the obtained emulsion increases, the particle size decreases, and the surface area of ​​the latex particles also increases, making it difficult for the shell layer to cover it, so that the impact strength, coloring and fluidity of the ASA resin high rubber powder are reduced, and it cannot meet user needs. Based on this, on the one hand, researchers in this field have been committed to developing ASA rubber powder and its preparation process, and are committed to controlling its particle size and structure to improve its performance.

[0006] On the other hand, the existing ASA materials have a relatively complex preparation method, the obtained ASA materials have low weather resistance and short service life, and are not suitable for use in harsh environments, which will limit the use of ASA materials in the fields of automobiles, outdoor building materials, etc. Therefore, developing an ASA colloid that can significantly improve the weather resistance of ASA resin without affecting its impact strength, fluidity and other properties is a research focus in this field. Summary of the invention

[0007] In view of the above problems, the present invention provides a highly weather-resistant ASA rubber powder and a preparation method thereof. The ASA rubber powder comprises a three-layer structure of a core layer, a nucleus layer and a shell layer from the inside out, silicone rubber emulsion is added to the nucleus layer, modified nano-montmorillonite is grafted on the shell layer, and a composite antioxidant is added. By optimizing the preparation method, the weather resistance of the ASA rubber particles can be significantly improved without affecting the performance of the ASA rubber particles such as impact strength and fluidity.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] On the one hand, the present invention provides a highly weather-resistant ASA rubber powder, which comprises a three-layer structure of a core layer, a core layer and a shell layer from the inside to the outside; the particle size of the highly weather-resistant ASA rubber powder is 400-600nm;

[0010] The core layer comprises the following components in terms of weight:

[0011] 30-45 parts of styrene;

[0012] 10-20 parts of acrylonitrile;

[0013] Emulsifier 0.2-1.5 parts;

[0014] 0.1-0.5 parts of trimethylolpropane trimethacrylate;

[0015] 0.8-1.5 parts of vinyltriethoxysilane;

[0016] 15-25 parts of silicone rubber emulsion;

[0017] Initiator 0.2-0.6 parts;

[0018] 30-50 parts of water.

[0019] Preferably, the particle size of the highly weather-resistant ASA rubber powder is 460-580 nm.

[0020] Preferably, the core layer comprises the following components in parts by weight:

[0021] 30-40 parts of styrene;

[0022] Acrylonitrile 12-18 parts;

[0023] Emulsifier 0.5-1.5 parts;

[0024] 0.1-0.3 parts of trimethylolpropane trimethacrylate;

[0025] 0.8-1.0 part of vinyltriethoxysilane;

[0026] 15-20 parts of silicone rubber emulsion;

[0027] Initiator 0.2-0.5 parts;

[0028] 40-50 parts of water.

[0029] Further preferably, the raw materials of the core layer include the following components in parts by weight:

[0030] Styrene 38 parts;

[0031] 15 parts of acrylonitrile;

[0032] Emulsifier 0.8 part;

[0033] 0.24 parts of trimethylolpropane trimethacrylate;

[0034] 0.8 parts of vinyltriethoxysilane;

[0035] Silicone rubber emulsion 18 parts;

[0036] Initiator 0.4 parts;

[0037] 50 parts of water.

[0038] Preferably, the initiator is selected from at least one of persulfate, thiosulfate and bisulfite;

[0039] Further preferably, the initiator is persulfate;

[0040] More preferably, the initiator is ammonium persulfate.

[0041] Preferably, the silicone rubber emulsion comprises the following components in parts by weight: 10-20 parts of methyl methacrylate, 5-12 parts of 2-ethylhexyl acrylate, 3-8 parts of butyl acrylate, 10-20 parts of styrene, 30-40 parts of silicone rubber, 1-2 parts of allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, 0.5-1 parts of antioxidant 1010, 0.5-1 parts of sodium persulfate, and 5-20 parts of water;

[0042] Further preferably, the silicone rubber emulsion comprises the following components in parts by weight: 18 parts of methyl methacrylate, 10 parts of 2-ethylhexyl acrylate, 8 parts of butyl acrylate, 16 parts of styrene, 35 parts of silicone rubber, 1.2 parts of allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, 0.5 parts of antioxidant 1010, 0.6 parts of sodium persulfate, and 20 parts of water;

[0043] Preferably, the preparation method of the silicone rubber emulsion is to prepare silicone rubber modified acrylic emulsion by emulsion polymerization of methyl methacrylate, 2-ethylhexyl acrylate, butyl acrylate, styrene, silicone rubber, allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], sodium persulfate and water;

[0044] Preferably, the emulsion polymerization conditions are: temperature 40-60° C., time 30-40 min.

[0045] Preferably, the core layer comprises the following components in parts by weight:

[0046] Butyl acrylate 90-110 parts;

[0047] 2.5-5 parts of methylpropionamide;

[0048] Emulsifier 4-10 parts;

[0049] 5-10 parts of initiator;

[0050] Antioxidant DLTP 6-10 parts;

[0051] 150-180 parts of water.

[0052] Further preferably, the core layer comprises the following components in parts by weight:

[0053] Butyl acrylate 90-100 parts;

[0054] 4 parts of methylpropionamide;

[0055] Emulsifier 5-8 parts;

[0056] 5-8 parts of initiator;

[0057] Antioxidant DLTP 6-10 parts;

[0058] 150-180 parts of water.

[0059] More preferably, the core layer comprises the following components in parts by weight:

[0060] Butyl acrylate 105 parts;

[0061] 4 parts of methylpropionamide;

[0062] 8 parts of emulsifier;

[0063] 6 parts of initiator;

[0064] Antioxidant DLTP 6 parts;

[0065] 160 parts of water.

[0066] Preferably, the shell layer comprises the following components in parts by weight:

[0067] 40-60 parts of styrene;

[0068] 10-20 parts of acrylonitrile;

[0069] 2-5 parts of methyl methacrylate;

[0070] Emulsifier 0.2-2 parts;

[0071] Initiator 0.2-1 part;

[0072] 1-2 parts of modified nano-montmorillonite;

[0073] 0.5-1 part of compound antioxidant;

[0074] 1-2 parts of pentaerythritol triallyl ester;

[0075] 40-100 parts of water;

[0076] Further preferably, the shell layer comprises the following components in parts by weight:

[0077] 48 parts of styrene;

[0078] Acrylonitrile 19 parts;

[0079] 1.5 parts of emulsifier;

[0080] 1 part of initiator;

[0081] 1.8 parts of modified nano-montmorillonite;

[0082] 0.6 parts of compound antioxidant;

[0083] 1.6 parts of pentaerythritol triallyl ester;

[0084] 80 parts water;

[0085] Preferably, the preparation method of the modified nano-montmorillonite is:

[0086] Hexadecyltrimethylammonium bromide and montmorillonite are stirred in a mixed solution of ethanol and water with a volume fraction of 60-80% for 1-3 hours, filtered and dried.

[0087] Preferably, the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1-1.5:2-4; further preferably, the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1.2:4.

[0088] Preferably, the composite antioxidant is a mixture of tris[2,4-di-tert-butylphenyl]phosphite and antioxidant BHT;

[0089] Preferably, the mass ratio of tris[2,4-di-tert-butylphenyl]phosphite to the antioxidant BHT is 0.4-0.8:1;

[0090] Further preferably, the mass ratio of tris[2.4-di-tert-butylphenyl]phosphite to the antioxidant BHT is 0.6:1;

[0091] Preferably, the emulsifier is sodium allyl ether hydroxypropane sulfonate;

[0092] Preferably, the initiator is at least one selected from persulfate, thiosulfate, and bisulfite;

[0093] Further preferably, the initiator is persulfate;

[0094] More preferably, the initiator is ammonium persulfate.

[0095] Preferably, the mass ratio of the core layer: the core layer: the shell layer is 30-40: 25-40: 25-30; further preferably, the mass ratio of the core layer: the core layer: the shell layer is 35: 28: 30.

[0096] On the other hand, the present invention provides a method for preparing highly weather-resistant ASA rubber powder, comprising the following steps:

[0097] S1: mixing butyl acrylate, methyl propionamide, emulsifier, antioxidant DLTP and water, pre-emulsifying, and then adding initiator for polymerization to obtain a core layer emulsion;

[0098] S2: The core layer emulsion is mixed with styrene, acrylonitrile, emulsifier, trimethylolpropane trimethacrylate, vinyl triethoxysilane, silicone rubber emulsion and water, and an initiator is added for polymerization to obtain a double-layer structure of a core layer wrapped in a core layer;

[0099] S3: The double-layer structure of the core layer wrapped by the core layer obtained in S2 is mixed with styrene 48, acrylonitrile, emulsifier, modified nano-montmorillonite, composite antioxidant, pentaerythritol triallyl ester and water at 45-60° C. for 20-30 minutes, and an initiator is added for polymerization, condensation, aging, dehydration and drying.

[0100] Preferably, in S1, the pre-emulsification temperature is 35-45°C, the stirring rate is 120-260r / min, and the time is 20-30min;

[0101] Preferably, in S1, the polymerization temperature is 55-60°C;

[0102] Preferably, in S2, the polymerization temperature is 60-70°C;

[0103] Preferably, in S3, the polymerization temperature is 75-85°C.

[0104] Compared with the prior art, the present invention has the following beneficial effects:

[0105] 1. The ASA rubber powder provided by the present invention has a three-layer structure, which includes a core layer, a core layer and a shell layer from the inside to the outside. When preparing the core layer, specific components and ratios are optimized; when preparing the core layer, silicone rubber emulsion is added; when preparing the shell layer, modified nano-montmorillonite and a composite antioxidant are added; while ensuring the impact strength performance of the ASA rubber particles, its weather resistance is significantly improved.

[0106] 2. The present invention optimizes the monomer components and ratios and the preparation method, thereby significantly improving the weather resistance of the ASA particles while ensuring their impact strength. DETAILED DESCRIPTION

[0107] In order to make the technical means, creative features, purpose and effect of the present invention easy to understand, the present invention is further explained below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without making creative work all belong to the protection scope of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited. The technology and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0108] Example 1

[0109] A highly weather-resistant ASA rubber powder, comprising a three-layer structure of a core layer, a nucleus layer and a shell layer from the inside to the outside;

[0110] The core layer, raw materials are calculated by weight and include the following components:

[0111] Styrene 38 parts;

[0112] 15 parts of acrylonitrile;

[0113] 0.8 parts of sodium allyl ether hydroxypropane sulfonate;

[0114] 0.24 parts of trimethylolpropane trimethacrylate;

[0115] 0.8 parts of vinyltriethoxysilane;

[0116] Silicone rubber emulsion 18 parts;

[0117] 0.4 parts of ammonium sulfate;

[0118] 50 parts of water.

[0119] The core layer, raw materials by weight, comprises the following components:

[0120] Butyl acrylate 105 parts;

[0121] 4 parts of methylpropionamide;

[0122] 8 parts of sodium allyl ether hydroxypropane sulfonate;

[0123] 6 parts of ammonium sulfate;

[0124] 6 parts of antioxidant DLTP;

[0125] 160 parts of water.

[0126] The shell layer, raw materials are calculated by weight and include the following components:

[0127] 48 parts of styrene;

[0128] Acrylonitrile 19 parts;

[0129] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0130] 1 part ammonium sulfate;

[0131] 1.8 parts of modified nano-montmorillonite;

[0132] 0.225 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0133] Antioxidant BHT 0.375 parts;

[0134] 1.6 parts of pentaerythritol triallyl ester;

[0135] 80 parts water;

[0136] The silicone rubber emulsion comprises the following components by weight: 18 parts of methyl methacrylate, 10 parts of 2-ethylhexyl acrylate, 8 parts of butyl acrylate, 16 parts of styrene, 35 parts of silicone rubber, 1.2 parts of allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, 0.5 parts of antioxidant 1010, 0.6 parts of sodium persulfate, and 20 parts of water;

[0137] The preparation method of the silicone rubber emulsion is as follows: methyl methacrylate, 2-ethylhexyl acrylate, butyl acrylate, styrene, silicone rubber, allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], sodium persulfate, and water are emulsion polymerized at 45° C. for 30 minutes to obtain a silicone rubber modified acrylic emulsion;

[0138] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0139] The preparation method of the modified nano-montmorillonite is:

[0140] 12 parts of hexadecyltrimethylammonium bromide and 40 parts of montmorillonite were stirred in a mixed solution of 75% by volume ethanol and water for 2 hours, filtered and dried.

[0141] The method for preparing the above-mentioned highly weather-resistant ASA rubber powder comprises the following steps:

[0142] S1: Butyl acrylate, methyl propionamide, emulsifier, antioxidant DLTP and water were mixed, stirred at 35°C for 25 minutes at a stirring rate of 200 r / min for pre-emulsification, and then an initiator was added to polymerize at 55°C to obtain a core layer emulsion;

[0143] S2: The core layer emulsion is mixed with styrene, acrylonitrile, emulsifier, trimethylolpropane trimethacrylate, vinyl triethoxysilane, silicone rubber emulsion and water, and an initiator is added to polymerize at 70°C to obtain a double-layer structure of a core layer wrapped in a core layer;

[0144] S3: The double-layer structure of the core layer wrapped by the core layer obtained in S2 is mixed with styrene 48, acrylonitrile, emulsifier, modified nano-montmorillonite, composite antioxidant, pentaerythritol triallyl ester and water at 45-60°C for 20-30 minutes, and an initiator is added to polymerize at 80°C, condense, mature, dehydrate and dry.

[0145] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0146] Example 2

[0147] A highly weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: the core layer, the raw materials are calculated by weight, and include the following components:

[0148] 45 parts of styrene;

[0149] 20 parts of acrylonitrile;

[0150] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0151] 0.1 parts of trimethylolpropane trimethacrylate;

[0152] 1.5 parts of vinyltriethoxysilane;

[0153] Silicone rubber emulsion 15 parts;

[0154] 0.2 parts of ammonium sulfate;

[0155] 45 parts of water.

[0156] The core layer, raw materials by weight, comprises the following components:

[0157] Butyl acrylate 90 parts;

[0158] 2.5 parts of methylpropionamide;

[0159] 4 parts of sodium allyl ether hydroxypropane sulfonate;

[0160] 10 parts of ammonium sulfate;

[0161] Antioxidant DLTP 10 parts;

[0162] 180 parts of water.

[0163] The shell layer, raw materials are calculated by weight and include the following components:

[0164] 60 parts of styrene;

[0165] 15 parts of acrylonitrile;

[0166] 0.2 parts of sodium allyl ether hydroxypropane sulfonate;

[0167] 0.2 parts of ammonium sulfate;

[0168] 1 part of modified nano-montmorillonite;

[0169] 0.375 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0170] Antioxidant BHT 0.625 parts;

[0171] 1 part of pentaerythritol triallyl ester;

[0172] 60 parts of water;

[0173] The mass ratio of the core layer: core layer: shell layer is 30:40:25

[0174] The rest is the same as Example 1, and the particle size of the high weather-resistant ASA rubber powder is 460-580nm.

[0175] Example 3

[0176] A highly weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: the core layer, the raw materials are calculated by weight, and include the following components:

[0177] 30 parts of styrene;

[0178] 10 parts of acrylonitrile;

[0179] 0.2 parts of sodium allyl ether hydroxypropane sulfonate;

[0180] 0.5 parts of trimethylolpropane trimethacrylate;

[0181] 1.0 part of vinyltriethoxysilane;

[0182] 25 parts of silicone rubber emulsion;

[0183] 0.6 parts of ammonium sulfate;

[0184] 30 parts water.

[0185] The core layer, raw materials by weight, comprises the following components:

[0186] Butyl acrylate 110 parts;

[0187] 5 parts of methylpropionamide;

[0188] 10 parts of sodium allyl ether hydroxypropane sulfonate;

[0189] 5 parts of ammonium sulfate;

[0190] Antioxidant DLTP 6 parts;

[0191] 150 parts of water.

[0192] The shell layer, raw materials are calculated by weight and include the following components:

[0193] 40 parts of styrene;

[0194] 20 parts of acrylonitrile;

[0195] 2 parts of sodium allyl ether hydroxypropane sulfonate;

[0196] 0.5 parts of ammonium sulfate;

[0197] 2 parts of modified nano-montmorillonite;

[0198] 0.187 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0199] Antioxidant BHT 0.313 parts;

[0200] 2 parts of pentaerythritol triallyl ester;

[0201] 100 parts water;

[0202] The rest is the same as Example 1.

[0203] The mass ratio of the core layer: the core layer: the shell layer is 40:25:25.

[0204] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0205] Comparative Example 1

[0206] A highly weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: the core layer, the raw materials are calculated by weight, and include the following components:

[0207] Styrene 50 parts;

[0208] 25 parts of acrylonitrile;

[0209] 0.1 parts of sodium allyl ether hydroxypropane sulfonate;

[0210] 0.4 parts of trimethylolpropane trimethacrylate;

[0211] 2 parts of vinyltriethoxysilane;

[0212] Silicone rubber emulsion 18 parts;

[0213] 0.4 parts of ammonium sulfate;

[0214] 27.34 parts of water.

[0215] The core layer, raw materials by weight, comprises the following components:

[0216] Butyl acrylate 80 parts;

[0217] 6 parts of methylpropionamide;

[0218] 12 parts of sodium allyl ether hydroxypropane sulfonate;

[0219] 4 parts of ammonium sulfate;

[0220] Antioxidant DLTP 11 parts;

[0221] 176 parts of water.

[0222] The shell layer, raw materials are calculated by weight and include the following components:

[0223] Styrene 65 parts;

[0224] Acrylonitrile 9 parts;

[0225] 2.2 parts of sodium allyl ether hydroxypropane sulfonate;

[0226] 1.5 parts of ammonium sulfate;

[0227] 3 parts of modified nano-montmorillonite;

[0228] 1 part of tris[2,4-di-tert-butylphenyl]phosphite;

[0229] Antioxidant BHT 1.6 parts;

[0230] 0.5 parts of pentaerythritol triallyl ester;

[0231] Water 69.7 parts;

[0232] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0233] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0234] The rest is the same as Example 1.

[0235] Comparative Example 2

[0236] A highly weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: the core layer, the raw materials are calculated by weight, and include the following components:

[0237] Styrene 28 parts;

[0238] 22 parts of acrylonitrile;

[0239] 0.1 parts of sodium allyl ether hydroxypropane sulfonate;

[0240] 0.6 parts of trimethylolpropane trimethacrylate;

[0241] 0.7 parts of vinyltriethoxysilane;

[0242] Silicone rubber emulsion 26 parts;

[0243] 0.1 part of ammonium sulfate;

[0244] 44.84 parts of water.

[0245] The core layer, raw materials by weight, comprises the following components:

[0246] Butyl acrylate 85 parts;

[0247] 6 parts of methylpropionamide;

[0248] 3.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0249] 4.5 parts of ammonium sulfate;

[0250] Antioxidant DLTP 12 parts;

[0251] 178 parts of water.

[0252] The shell layer, raw materials are calculated by weight and include the following components:

[0253] Styrene 39 parts;

[0254] 8 parts of acrylonitrile;

[0255] 6 parts of sodium allyl ether hydroxypropane sulfonate;

[0256] 0.1 part of ammonium sulfate;

[0257] 2.2 parts of modified nano-montmorillonite;

[0258] 0.8 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0259] Antioxidant BHT 2 parts;

[0260] Pentaerythritol triallyl ester 2.5 parts;

[0261] Water 92.9 parts;

[0262] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0263] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0264] The remaining operations are the same as those in Example 1.

[0265] Comparative Example 3

[0266] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0267] The core layer, raw materials are calculated by weight and include the following components:

[0268] Styrene 38 parts;

[0269] 15 parts of acrylonitrile;

[0270] 0.8 parts of sodium allyl ether hydroxypropane sulfonate;

[0271] 0.24 parts of trimethylolpropane trimethacrylate;

[0272] 0.8 parts of vinyltriethoxysilane;

[0273] 0.4 parts of ammonium sulfate;

[0274] 68 parts of water.

[0275] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0276] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0277] The remaining operations are the same as those in Example 1.

[0278] Comparative Example 4

[0279] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0280] The silicone rubber emulsion comprises the following components by weight: 8 parts of methyl methacrylate, 4 parts of 2-ethylhexyl acrylate, 2 parts of butyl acrylate, 22 parts of styrene, 45 parts of silicone rubber, 0.6 parts of allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, 0.1 parts of antioxidant 1010, 1.2 parts of sodium persulfate, and 21.3 parts of water;

[0281] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0282] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0283] The remaining operations are the same as those in Example 1.

[0284] Comparative Example 5

[0285] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0286] The shell layer, raw materials are calculated by weight and include the following components:

[0287] 48 parts of styrene;

[0288] Acrylonitrile 19 parts;

[0289] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0290] 1 part ammonium sulfate;

[0291] 0.225 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0292] Antioxidant BHT 0.375 parts;

[0293] 1.6 parts of pentaerythritol triallyl ester;

[0294] Water 81.8 parts;

[0295] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0296] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0297] The remaining operations are the same as those in Example 1.

[0298] Comparative Example 6

[0299] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: Shell layer, raw materials are calculated by weight, comprising the following components:

[0300] 48 parts of styrene;

[0301] Acrylonitrile 19 parts;

[0302] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0303] 1 part ammonium sulfate;

[0304] 1.8 parts of modified nano-montmorillonite;

[0305] 0.6 parts of tris[2,4-di-tert-butylphenyl]phosphite;

[0306] 1.6 parts of pentaerythritol triallyl ester;

[0307] 80 parts water;

[0308] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0309] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0310] The remaining operations are the same as those in Example 1.

[0311] Comparative Example 7

[0312] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: Shell layer, raw materials are calculated by weight, comprising the following components:

[0313] 48 parts of styrene;

[0314] Acrylonitrile 19 parts;

[0315] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0316] 1 part ammonium sulfate;

[0317] 1.8 parts of modified nano-montmorillonite;

[0318] Antioxidant BHT 0.6 parts;

[0319] 1.6 parts of pentaerythritol triallyl ester;

[0320] 80 parts water;

[0321] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0322] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0323] The remaining operations are the same as those in Example 1.

[0324] Comparative Example 8

[0325] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, specifically as follows: Shell layer, raw materials are calculated by weight, comprising the following components:

[0326] 48 parts of styrene;

[0327] Acrylonitrile 19 parts;

[0328] 1.5 parts of sodium allyl ether hydroxypropane sulfonate;

[0329] 1 part ammonium sulfate;

[0330] 1.8 parts of modified nano-montmorillonite;

[0331] Antioxidant DLTP 0.6 part;

[0332] 1.6 parts of pentaerythritol triallyl ester;

[0333] 80 parts water;

[0334] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0335] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0336] The remaining operations are the same as those in Example 1.

[0337] Comparative Example 9

[0338] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0339] 48 parts of styrene;

[0340] Acrylonitrile 19 parts;

[0341] 1.5 parts of emulsifier;

[0342] 1 part of initiator;

[0343] 1.8 parts of nano-montmorillonite;

[0344] 0.6 parts of compound antioxidant;

[0345] 1.6 parts of pentaerythritol triallyl ester;

[0346] 80 parts water;

[0347] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0348] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0349] The remaining operations are the same as those in Example 1.

[0350] Comparative Example 10

[0351] A high weather-resistant ASA rubber powder, compared with Example 1, only the formula is different, as follows:

[0352] Sodium lauryl sulfate was used to replace the emulsifier sodium allyl ether hydroxypropane sulfonate;

[0353] The mass ratio of the core layer: the core layer: the shell layer is 35:28:30.

[0354] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0355] The remaining operations are the same as those in Example 1.

[0356] Comparative Example 11

[0357] A high weather-resistant ASA rubber powder, compared with Example 1, only the mass ratio of core layer:nucleus layer:shell layer is changed to 32:34:38.

[0358] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0359] The remaining operations are the same as those in Example 1.

[0360] Comparative Example 12

[0361] A high weather-resistant ASA rubber powder, compared with Example 1, only the mass ratio of core layer:nuclear layer:shell layer is changed to 25:42:22.

[0362] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0363] The remaining operations are the same as those in Example 1.

[0364] Comparative Example 13

[0365] A highly weather-resistant ASA rubber powder, compared with Example 1, only the preparation method is different:

[0366] The method for preparing the above-mentioned highly weather-resistant ASA rubber powder comprises the following steps:

[0367] S1: Butyl acrylate, methyl propionamide, emulsifier, antioxidant DLTP and water were mixed, stirred at 25°C for 40 minutes at a stirring rate of 300 r / min for pre-emulsification, and then an initiator was added to polymerize at 85°C to obtain a core layer emulsion;

[0368] S2: The core layer emulsion is mixed with styrene, acrylonitrile, emulsifier, trimethylolpropane trimethacrylate, vinyl triethoxysilane, silicone rubber emulsion and water, and an initiator is added to polymerize at 55°C to obtain a double-layer structure of a core layer wrapped in a core layer;

[0369] S3: The double-layer structure of the core layer wrapped by the core layer obtained in S2 is mixed with styrene 48, acrylonitrile, emulsifier, modified nano-montmorillonite, composite antioxidant, pentaerythritol triallyl ester and water at 45-60°C for 20-30 minutes, and an initiator is added to polymerize at 65°C, condense, mature, dehydrate and dry.

[0370] The particle size of the highly weather-resistant ASA rubber powder is 460-580nm.

[0371] The remaining operations are the same as those in Example 1.

[0372] Test Case

[0373] The high weather-resistant ASA rubber powder prepared in Examples 1-3 of the present invention and Comparative Examples 1-13 was mixed with SAN resin in a mass ratio of 3:7, stirred at 1000 r / min for 15 min, and then added to a twin-screw extruder. After melting, extrusion, shaping, and drying, test samples were obtained and performance tests were performed.

[0374] Parameters of the twin-screw extruder: main engine speed: 160r / min, feeding speed: 55r / min, aspect ratio of the extruder: 36, reference temperatures of the four sections of screw heating: zone 1 temperature 190℃, zone 2 temperature 235℃, zone 3 temperature 235℃, zone 4 temperature 280℃, residence time 3min, pressure 18Mpa.

[0375] Notched impact strength: The notched impact strength of the sample is measured in accordance with GB / T1843-2008 "Determination of Izod Impact Strength of Plastics" at a temperature of 23°C.

[0376] Melt index: According to GB / T3682 "Test method for melt flow rate of thermoplastics", the melt flow rate tester of the high-speed rail testing company is used Determine the melt index.

[0377] Weather resistance: Test the weather resistance of high gloss surface according to SAE J2527 standard, evaluate the color difference △E, and the total radiation dose is 2500kJ / m 2 The larger the △E, the worse the weather resistance. It is generally considered that △E ≥ 3 is unqualified.

[0378] Heat deformation temperature: using ISO 75-1A method (flat, load 1.8MPa, heating rate 120℃ / h), sample without annealing treatment, sample thickness 4mm.

[0379] Table 1. Performance test results

[0380]

[0381]

[0382] From the data in Table 1, it can be seen that, compared with Comparative Examples 1-13, Examples 1-3 have better weather resistance and heat resistance while ensuring the impact strength and melt index of the product. This shows that the present invention significantly improves the weather resistance of the ASA granules while ensuring the impact strength performance through a specific structure, specific components and their proportions, and by optimizing the preparation method.

[0383] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A highly weather-resistant ASA rubber powder, characterized in that: From the inside to the outside, it includes a core layer, a core layer and a shell layer. The particle size of the high weather-resistant ASA rubber powder is 400-600nm. The core layer comprises the following components in terms of weight: 30-45 parts of styrene; 10-20 parts of acrylonitrile; Emulsifier 0.2-1.5 parts; 0.1-0.5 parts of trimethylolpropane trimethacrylate; 0.8-1.5 parts of vinyltriethoxysilane; 15-25 parts of silicone rubber emulsion; Initiator 0.2-0.6 parts; 30-50 parts of water.

2. The highly weather-resistant ASA rubber powder according to claim 1, characterized in that: The core layer comprises the following components in terms of weight: 30-40 parts of styrene; Acrylonitrile 12-18 parts; Emulsifier 0.5-1.5 parts; 0.1-0.3 parts of trimethylolpropane trimethacrylate; 0.8-1.0 part of vinyltriethoxysilane; 15-20 parts of silicone rubber emulsion; Initiator 0.2-0.5 parts; 40-50 parts of water.

3. The highly weather-resistant ASA rubber powder according to claim 1, characterized in that: The initiator is selected from at least one of persulfate, thiosulfate and bisulfite.

4. The highly weather-resistant ASA rubber powder according to claim 1, characterized in that: The silicone rubber emulsion comprises the following components in parts by weight: 10-20 parts of methyl methacrylate, 5-12 parts of 2-ethylhexyl acrylate, 3-8 parts of butyl acrylate, 10-20 parts of styrene, 30-40 parts of silicone rubber, 1-2 parts of allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, 0.5-1 parts of antioxidant 1010, 0.5-1 parts of sodium persulfate, and 5-20 parts of water.

5. The highly weather-resistant ASA rubber powder according to claim 4, characterized in that: The preparation method of the silicone rubber emulsion is as follows: methyl methacrylate, 2-ethylhexyl acrylate, butyl acrylate, styrene, silicone rubber, allyloxy nonylphenoxy propanol polyoxyethylene ether SN-15, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], sodium persulfate and water are subjected to emulsion polymerization to obtain silicone rubber modified acrylic emulsion.

6. The highly weather-resistant ASA rubber powder according to claim 1, characterized in that: The core layer comprises the following components in terms of weight: Butyl acrylate 90-110 parts; 2.5-5 parts of methylpropionamide; Emulsifier 4-10 parts; 5-10 parts of initiator; Antioxidant DLTP 6-10 parts; 150-180 parts of water.

7. The highly weather-resistant ASA rubber powder according to claim 6, characterized in that: The core layer comprises the following components in terms of weight: Butyl acrylate 90-100 parts; 4 parts of methylpropionamide; Emulsifier 5-8 parts; 5-8 parts of initiator; Antioxidant DLTP 6-10 parts; 150-180 parts of water.

8. The highly weather-resistant ASA rubber powder according to claim 1, characterized in that: The shell layer, the raw materials are calculated by weight, and include the following components: 40-60 parts of styrene; 10-20 parts of acrylonitrile; 2-5 parts of methyl methacrylate; Emulsifier 0.2-2 parts; Initiator 0.2-1 part; 1-2 parts of modified nano-montmorillonite; 0.5-1 part of compound antioxidant; 1-2 parts of pentaerythritol triallyl ester; 40-100 parts of water.

9. The highly weather-resistant ASA rubber powder according to claim 8, characterized in that: The preparation method of the modified nano-montmorillonite is: Hexadecyltrimethylammonium bromide and montmorillonite are stirred in a mixed solution of ethanol and water with a volume fraction of 60-80% for 1-3 hours, filtered and dried.

10. The highly weather-resistant ASA rubber powder according to claim 9, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1-1.5:2-4.

11. The highly weather-resistant ASA rubber powder according to claim 8, characterized in that: The composite antioxidant is a mixture of tris[2,4-di-tert-butylphenyl]phosphite and antioxidant BHT.

12. The highly weather-resistant ASA rubber powder according to claim 11, characterized in that: The mass ratio of the tris[2.4-di-tert-butylphenyl]phosphite to the antioxidant BHT is 0.4-0.8:

1.

13. The highly weather-resistant ASA rubber powder according to claim 8, characterized in that: The emulsifier is sodium allyl ether hydroxypropane sulfonate.

14. The method for preparing the highly weather-resistant ASA rubber powder according to any one of claims 1 to 13, characterized in that: The following steps are involved: S1: mixing butyl acrylate, methyl propionamide, emulsifier, antioxidant DLTP and water, pre-emulsifying, and then adding initiator for polymerization to obtain a core layer emulsion; S2: The core layer emulsion is mixed with styrene, acrylonitrile, emulsifier, trimethylolpropane trimethacrylate, vinyl triethoxysilane, silicone rubber emulsion and water, and an initiator is added for polymerization to obtain a double-layer structure of a core layer wrapped in a core layer; S3: The double-layer structure of the core layer wrapped by the core layer obtained in S2 is mixed with styrene 48, acrylonitrile, emulsifier, modified nano-montmorillonite, composite antioxidant, pentaerythritol triallyl ester and water at 45-60° C. for 20-30 minutes, and an initiator is added for polymerization, condensation, aging, dehydration and drying.

15. The preparation method according to claim 14, characterized in that: In S1, the pre-emulsification temperature is 35-45°C, the stirring rate is 120-260r / min, and the time is 20-30min.

16. The preparation method according to claim 14, characterized in that: In S1, the polymerization temperature is 55-60°C; In S2, the polymerization temperature is 60-70°C; In S3, the polymerization temperature is 75-85°C.